Konsistensi RPP dengan Pelaksanaan Pembelajaran Sejarah - Suryadi Fajri (UIN Imam Bonjol Padang, 2023)
The background of this research is the Consistency of Lesson Plans with the Implementation of History Learning which was carried out in class XI IPS MAN 1 Padang City. In the implementation of learning, educators make great efforts to adapt the implementation of learning to the RPP which is used as a reference for learning at each meeting, even though it is not yet 100% consistent with the RPP they designed. At present there are many controversies regarding the consistency of the implementation of history learning with the RPP that has been designed. This study uses a qualitative phenomenological approach. In its application, this research further describes all the data and conditions of the subject or research object related to the consistency of the RPP with its implementation so that the data obtained can be analyzed and compared based on the current reality. The informants in this study were school principals, curriculum assistants, and history teachers in class XI IPS MAN 1 Padang City. After conducting research in the field, the results can be obtained that the implementation of history learning is not fully consistent with the RPP which is used as a reference because there are various obstacles and impacts that occur during the implementation of learning, one of which is the lack of enthusiasm for student learning when learning history takes place.